(untitled) (International Journal of Nursing Education, 2021)
Parents are the most powerful instruments in promoting good mental health. This study examined the relationship between parenting style and the mental health of female adolescents in Tabuk, KSA. The study employed a correlational methodology, using Convenience Sampling of 100 participants. Standardized questionnaires of Depression, Anxiety, and Stress Scale and Measure of Parental Style were distributed. Data were analyzed using Statistical Package for the Social Sciences (SPSS) Version 21.0. Majority of the respondents belong to 20 years of age (26%), were first- year students (34 %), from a nuclear family (77%) with five to six siblings (27%) and in the income bracket 15,000-25,000 SAR (25%). Parents were over controlling (maternal [73%] and paternal [65%]). There was a high rate of mental health problems among female adolescents, represented by anxiety (25%), stress (20%) and depression (18%).